(untitled) (INTEGRATION PROCEEDING, 2023)
Stunting is a condition of failure to grow in children that can be a benchmark for the low level of human resources in a nation. Basic Health Research in 2018 showed the prevalence of stunting in Indonesia, including health problems in the severe category with a percentage of 30.8%. Pregnancy history such as SEZ and anemia have an important role in the process of fetal growth and development until the time of birth so it is necessary to analyze the relationship with stunting events. To analyze the pregnancy history of stunting events at the Sungai Pinang Health Center. This study is of the analytical observational type with a quantitative design and cross-sectional approach. The research sample consisted of 46 respondents selected by purposive sampling technique. The statistical test used in this study was chi square. Most mothers had no history of SEZ (53.3%), no history of anemia (74.8%) and most children were not stunted (62.9%). The results of the chi square test showed that there was a relationship between the history of SEZ and the incidence of stunting (P = 0.000) and there was a relationship between the history of anemia and the incidence of stunting (P = 0.000). Mothers who do not have a history of SEZ pregnancy and anemia tend to have children who are not stunted at the Sungai Pinang Health Center.